VIOLATING POLITENESS PRINCIPLES IN CELLULAR PHONE PROVIDER - Handayani, Tuty (LANTERN (Journal on English Language, Culture and Literature), 2013)
In daily life, we need language to express our feeling. One of the language usages can be seen through the advertisement. The advertiser persuades the customers to use the product in many ways; one of them is through language. Language in television advertisement plays the important role to reach the goal of advertisement. Since we know that the viewers of television in Indonesia is about more than 128 million, we can imagine how strong the influence of television commercial is. To catch the viewer’s attention, the advertiser sometimes used some strategies. It is good if they use the polite language, but if they use the impolite language, it gives the bad impact to the viewer. In this thesis, the writer does not want to analyse the bad impact of language advertisement, but she prefers to analyse the kinds of politeness principles that are violated by the advertisements especially cellular phone provider. The purposes of this thesis are to find out what kind of politeness principles that are violated by the advertisement and to find out what is the intention of violating such principles. The writer classifies the violation through the six maxims of politeness principles by Leech (1983). In collecting the data, the writer used documentation method and non-participant observation. The population of this research are all the cellular phone provider advertisements in Indonesia, but the samples are chosen purposively, only the advertisements that violate the politeness principle that become the data of this research. In analysing the data, the writer uses the politeness principles theory proposed by Leech as the instrument of research, to classify the advertisement according to the maxim they violate. The writer also relates the violation with the ethic regulation of politeness principles proposed by Dewan Periklanan Indonesia. After analysing the kinds of maxim, the writer extends to the intention of violating through the explicature and implicature meaning. In this research, the writer found 12 advertisements that violated the politeness principles. The violations occur in six maxims of politeness principles, such as tact maxim, generosity maxim, approbation maxim, modesty maxim, agreement maxim and sympathy maxim. Most of advertisements that violate the politeness principles also violate the ethic regulation of advertisement. Then, the general intentions of those violations were to attract the viewer’s attention to use their product. Keywords: Politeness Principles, Verbal Advertisement, Ethic Regulation of Advertisement, Explicature and Implicature Meaning